1996
DOI: 10.1007/bf01798116
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the non-invasive localization accuracy of cardiac arrhythmias attainable by multichannel magnetocardiography (MCG)

Abstract: The accuracy of multichannel magnetocardiography (MCG) for the non-invasive localization of cardiac arrhythmias was investigated. A non-magnetic catheter was used in phantom studies and for cardiac pacing of 6 patients. In a clinical setting, 32 patients with WPW-syndrome, 37 patients with premature ventricular complexes and 12 patients with ventricular tachycardia were studied and the MCG results compared to reference methods, including invasive electrophysiological mapping. Phantom and pacing studies demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 26 publications
0
18
1
2
Order By: Relevance
“…The box model (mean 3-D error of 36 mm) was better than the halfspace, but not as good as the sphere. (Table I) The present results are somewhat different from those of previous studies, which in the clinical setting, most often have used the infinite halfspace and found the error to be in the range 18-73 mm [7], [11], [13]- [16], [18], [20]. A strict comparison is, however, difficult since some earlier studies applied other reference methods such as standard ECG [16], body surface mapping, coronary sinus mapping [7], [13]- [16], epicardial intraoperative mapping [16], [17], [19], radionuclide ventriculography [7] and temporary pacing site [21], while we have used the best presently available clinical reference method, i.e., the site of successful RF-ablation.…”
Section: Discussioncontrasting
confidence: 99%
“…The box model (mean 3-D error of 36 mm) was better than the halfspace, but not as good as the sphere. (Table I) The present results are somewhat different from those of previous studies, which in the clinical setting, most often have used the infinite halfspace and found the error to be in the range 18-73 mm [7], [11], [13]- [16], [18], [20]. A strict comparison is, however, difficult since some earlier studies applied other reference methods such as standard ECG [16], body surface mapping, coronary sinus mapping [7], [13]- [16], epicardial intraoperative mapping [16], [17], [19], radionuclide ventriculography [7] and temporary pacing site [21], while we have used the best presently available clinical reference method, i.e., the site of successful RF-ablation.…”
Section: Discussioncontrasting
confidence: 99%
“…MCG has proven accurate in localization of accessory pathways causing pre-excitation in Wolff-Parkinson-White syndrome [64], as well as in localization of the tachycardia points of origin [65] and premature ventricular ectopic complexes [66]. MCG have been superior to signal-averaged ECG in indicating a propensity toward life-threatening arrhythmias and magnetocardiographic intra-QRS fragmentation [67] and QT dispersion have identified post-MI patients prone to ventricular arrhythmias [68], the former being independent of the extent of LV dysfunction.…”
Section: Mcg Studies At Rhythm Disordersmentioning
confidence: 99%
“…However, in 1998, using the Helsinki multichannel system with an acceptable signal-to-noise ratio, Fenici et al demonstrated that MCG is an effective clinical tool for non-invasive threedimensional electro-anatomical imaging [41]. Accurate localization of the accessory pathway has been successfully performed in patients with Wolf-ParkinsonWhite (WPW) syndrome [42][43][44][45][46]. In these studies the accuracy of the non-invasive MCG localization of arrhythmogenic substrates has been evaluated by comparison with the results of conventional invasive catheter mapping.…”
Section: Rozkład Prądów Nasierdziowych U Pacjenta Z Ciasnym Zwężenimentioning
confidence: 99%